La relation enseignant-élèves au cœur de la réussite éducative - Séverine Haiat; Gaelle Espinosa; Annie Charron (Éducation et Socialisation)
Many French and English studies indicate that the teacher-student relationship is a key to students’ educational success, and to the the well-being of both children and their teachers at school. This relationship is considered here as a whole, encompassing teacher attributes, teacher and student perceptions and representations, and teacher-student interactions. In this theoretical and reflexive article, we present different locutions that are tied to the concept of teacher-student relationships. We explain the Teaching through Interactions model, an internationally recognized approach to help better understand the importance of quality interactions in educational contexts. Given this model’s connection with international educational recommendations, it suggests avenues for thinking about how to shift teacher practices and improve relationships with students.